Psychiatric nurses versus psychiatrists and pharmacists 'knowledge on polypharmacy practices in psychiatry: An interprofessional mixed-methods exploration - Amal I. Khalil; Alhanouf A. Almuhalbidi; Reema T. Almutairi; Shahad S. Almutairi; Hatun H. Alansari; Atheer S. Almarri; Shaima K. Alzahrani; Joud S. Alzahrani (PLoS ONE, 2026)
Background Polypharmacy is often crucial for managing complex and treatment-resistant psychiatric disorders, yet it carries risks such as adverse drug interactions, medication non-compliance, and suboptimal health outcomes. Interprofessional perspectives on polypharmacy significantly influence clinical decision-making and prescribing practices. Aim This research evaluates healthcare providers’ knowledge and attitudes regarding psychiatric polypharmacy, comparing the views of psychiatric nurses, psychiatrists, and pharmacists. It also explores how these factors impact prescribing behaviors and interprofessional collaboration. Methods A convergent mixed-methods approach was employed at the Erada Complex for Mental Health and Addiction in Jeddah, Saudi Arabia. The study involved 221 healthcare providers, including psychiatrists (n = 32), psychiatric nurses (n = 158), and pharmacists (n = 31). Quantitative data were collected using validated scales to assess knowledge and attitudes, while qualitative insights were gathered through open-ended responses and group discussions. Results Knowledge levels varied among the professionals, with psychiatrists possessing the most comprehensive understanding (84.2 ± 11.0), followed by pharmacists (81.5 ± 10.0) and psychiatric nurses (79.5 ± 9.8). Attitudes toward polypharmacy also differed, with psychiatrists showing the most favorable views (3.79 ± 0.49), whereas nurses and pharmacists were more cautious due to concerns about adverse effects and medication burden. A significant positive correlation (r = 0.653, p < 0.05) was observed between knowledge and attitude scores. Sociodemographic factors, such as professional experience and confidence in medication management, influenced both knowledge and attitudes regarding medication management. Qualitative findings highlighted interprofessional tensions, with psychiatric nurses advocating for more conservative approaches, psychiatrists emphasizing clinical necessity, and pharmacists focusing on optimizing medication safety. Conclusion Healthcare providers demonstrated varying levels of awareness and attitudes toward psychiatric polypharmacy, shaped by their professional roles and responsibilities. While psychiatrists were more accepting of polypharmacy, psychiatric nurses expressed concerns about patient burden, and pharmacists prioritized safety considerations. Enhancing interprofessional collaboration and ongoing education on polypharmacy practices are essential for improving patient outcomes.